An Investigation into the Association Between Intravenous Crystalloid Administration and Perioperative Nausea and Vomiting in Morbidly Obese Patients Undergoing Laparoscopic Sleeve Gastrectomy - Demirdag, Ahmet; Yildiz Altun, Aysun; Ozcan, Sibel; Aksu, Ahmet; Demirel, Ismail (Springer, 2025)
BackgroundLaparoscopic sleeve gastrectomy (LSG) is among the most commonly preferred surgical methods for the treatment of morbid obesity. Postoperative nausea and vomiting (PONV) is a significant complication that adversely affects patient comfort and recovery. This study aims to evaluate the effects of intravenous sodium chloride and dextrose solutions on PONV in patients undergoing LSG.Materials and MethodsIn this prospective randomized controlled study, 201 patients who underwent LSG were randomly assigned to two groups. Based on intravenous (IV) fluid management, patients received either 0.9% sodium chloride + 5% dextrose (Group 1) or 0.9% sodium chloride alone (Group 2). The incidence of PONV, antiemetic and analgesic consumption, and time to first mobilization were recorded at 0, 15, and 30 min, and at 6 and 24 h postoperatively.ResultsGroup 1 demonstrated a significantly lower incidence of nausea upon admission to the post-anesthesia care unit (PACU) and at the 15th postoperative minute compared to Group 2. However, at 24 h postoperatively, Group 1 exhibited higher rates of nausea and vomiting. Additionally, Group 1 required increased opioid and antiemetic administration, experienced longer times to initial mobilization, and had prolonged discharge durations relative to Group 2.ConclusionThis study suggests that intravenous fluids containing dextrose may reduce early postoperative PONV but are associated with increased nausea and vomiting in the later postoperative period, leading to greater analgesic and antiemetic requirements. Therefore, avoiding dextrose- containing IV fluids in morbidly obese patients scheduled for surgery may help reduce the incidence of postoperative nausea and vomiting.
Keywords: Morbid obesity; Sleeve gastrectomy; Postoperative nausea and vomiting; Intravenous fluids